Gangguan Perkembangan Seksual 46,XY: Sebuah Laporan Kasus dan Tinjauan Pustaka - Welni, Trisia; Fakhrurrazi, Fakhrurrazi (Majalah Kedokteran Indonesia, 2023)
Introduction: Disorder of sex development (DSD) is a condition characterized by atypical anatomy of the reproductive organs, making it difficult to clearly identify the genitalia. DSD cases encompass various types and causes. Among them, 46,XY DSD is a very rarely found disorder. This paper provides a case illustration and a literature review on 46,XY DSD.Case Report: A 7-year-old male child was brought by his parents due to the presence of ambiguous genitalia, which had been noted since birth. The child’s growth, development, and nutritional status were normal. Genital examination revealed a scrotum resembling labia majora, hypospadias, a penis size of approximately 2 cm, and symmetrically palpable scrotum and testes. Karyotyping analysis showed a 46,XY chromosomal pattern.Discussion: 46,XY DSD occured from defect in androgen synthesis and target cell resistance to androgens. Clinically, individuals with 46,XY DSD may present with ambiguous genitalia, cryptorchidism, hypospadias, and micropenis, although manifestations will vary depending on the type and degree of androgen hormone disorder. Diagnostic evaluations should include chromosomal analysis, assessment of sex steroid hormone levels, and imaging studies, such as pelvic ultrasound within 24 hours of birth, genitogram, and even MRI for evaluating Mullerian structures. The management of DSD is carried out by a multidisciplinary team, encompassing medical therapy, surgery, sex steroid replacement therapy, gender assignment, and psychosocial support.Conclusion: 46,XY DSD is a rare occurrence. Comprehensive diagnostic assessments are necessary for each DSD case to determine the type, cause, and comprehensive management in accordance with the etiology.